PREPARATION OF AVIATION INDUSTRY TRANSITION ON COVID-19 FROM PANDEMIC TO ENDEMIC PHASE: A REVIEW - Zakaria, Izatul Husna; Mohammad, Nur'Jila; Abashah, Aidanazima; Alshuaibi, Mohammad Said Ibrahim; Othman, Adilah; Ahmad, Nurazwa; Abu Yaziz, Mohd Fathi; Muslim Diekola Akanmu, Muslim Diekola Akanmu (JPB, 2023)
Purpose: The aim of this study is to examine the Malaysian government's actions towards the aviation industry to deal with the Covid-19 pandemic and the transition phase from pandemic to endemic. Transition phase refers to a temporary period before the country could fully enter the endemic phase which is subject to an announcement by the World Health Organisation (WHO).